Improved adjuvanting of seasonal influenza vaccines: Preclinical studies of MVA‐NP+M1 coadministration with inactivated influenza vaccine. Issue 7 (10th June 2013) - Mullarkey, Caitlin E.; Boyd, Amy; van Laarhoven, Arjan; Lefevre, Eric A.; Veronica Carr, B.; Baratelli, Massimiliano; Molesti, Eleonora; Temperton, Nigel J.; Butter, Colin; Charleston, Bryan; Lambe, Teresa; Gilbert, Sarah C.
<x xml:space="preserve">Abstract</x> Licensed seasonal influenza vaccines induce antibody (Ab) responses against influenza hemagglutinin (HA) that are limited in their ability to protect against different strains of influenza. Cytotoxic T lymphocytes recognizing the conserved internal nucleoprotein (NP) and matrix protein (M1) are capable of mediating a cross‐subtype immune response against influenza. Modified vaccinia Ankara (MVA) virus encoding NP and M1 (MVA‐NP+M1) is designed to boost preexisting T‐cell responses in adults in order to elicit a cross‐protective immune response. We examined the coadministration of HA protein formulations and candidate MVA‐NP+M1 influenza vaccines in murine, avian, and swine models. Ab responses postimmunization were measured by ELISA and pseudotype neutralization assays. Here, we demonstrate that MVA‐NP+M1 can act as an adjuvant enhancing Ab responses to HA while simultaneously inducing potent T‐cell responses to conserved internal Ags. We show that this regimen leads to the induction of cytophilic Ab isotypes that are capable of inhibiting hemagglutination and in the context of H5 exhibit cross‐clade neutralization. The simultaneous induction of T cells and Ab responses has the potential to improve seasonal vaccine performance and could be employed in pandemic situations.